(untitled) (Bangladesh Journal of Medical Microbiology, 2010)
In this prospective study out of 300 randomly selected clinically and/or radiologically suspected TB patients ultimately data of 277 cases were analyzed. Among 23 excluded cases, 6 were positive by microscopy, 5 responded with broad spectrum antibiotics, and 12 were contaminated. After 2 months follow up with anti TB drugs, a total of 124 TB cases were diagnosed of which 121 (44%)were culture positive. Three cases were diagnosed by empirical anti TB treatment. A total of 153 cases were true negative by mycobacterial culture. Of 121 isolates 119 were typical and 2 were atypical mycobacteria. In this group, the sensitivity, specificity, positive predictive value and negative predictive value of mycobacterial culture were 97.63%, 100%, 100% and 98.1% respectively. Among the culture proven cases; 79% were prevalent in male and 21% in female. Case positivity was significantly higher among patient having symptoms of cough with hemophtysis with or without fever(58%) than the patients with constitutional symptoms. No advanced or cavitary lesions were seen on X-ray among culture proven cases. Majority culture proven cases(72%) had minimal lesion on X-ray. After two months anti TB therapy 119 culture proven cases and three culture negative cases improved clinically and radiologically. Bangladesh J Med Microbiol 2010; 03 (02): 23-26